HUBUNGAN AKTIFITAS FISIK DENGAN KEJADIAN OBESITAS SENTRAL PADA PASIEN POLIKLINIK JANTUNG DAN PENYAKIT DALAM - Septiyanti, Septiyanti (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
The purpose of this study to determine the relationship between physical activityand the incidence of central obesity and heart disease clinic patients in Hospital Dr. M. YunusBengkulu 2014. This research is a cross-sectional method and sampling conducted byaccidental sampling technique. Independent variables (physical activity) and the dependentvariable (central obesity). Total population of 5,021 people with a total study sample was 96people. Results showed that there is a relationship between physical activity and the incidenceof central obesity (p = 0.000). It is expected that the clinic nurse to be able to improve thequality of health services, especially in patients who are at risk of central obesity andpreventive improvement can be done by preventing the increase in central obesity bychanging one's lifestyle by increasing activity on a regular basis.